Greek-Romanian Symbiotic Patterns in the Early Modern Period: History, Mentalities, Institutions - II - Panou, Nikos (The Historical Review/La Revue Historique, 2008)
This is the second part of a larger study seeking to contribute to a better understanding of the sustained process of religious, socio-political and cultural contact between Greek and Romanian ethnic groups in the early modern period. The two sections published here bring forward and discuss little-known and yet important evidence covering the first two post-Byzantine centuries and are intended to elaborate, supplement or contextualise the materials presented in the first part (which appeared in the previous volume of this journal). Not accidentally, this article ends with an unavoidable reference to the very text that ignited our exploration into the historical landscape of the pre-modern Balkans, a short but striking passage from Matthew of Myra’s early seventeenth-century chronicle known as History of Wallachia. Indeed, Matthew’s testimony stands out as one of the first conscious attempts to account for the uneasy, but also prolific, dynamic and multi-layered, relationship between the two peoples. It has been the aim of this paper to illustrate the basic patterns of that intricate, as much as intriguing, relationship as it was being shaped in the aftermath of the Byzantine Commonwealth’s absorption into the challenging world of the Ottoman Turks.